A New Species and Three New Records Belonging to Mucorales and Mortierellales from Korea - Thuong T. T. Nguyen; Ki Hyun Kang; Su Jin Kim; Min Kyung Kim; So Jeong Noh; Hyang Burm Lee (Mycobiology)
During an investigation of fungi of the orders Mucorales and Mortierellales in Korea, a new Backusella species, Backusella terrestris sp. nov., and three new records, Entomortierella sugadairana, Mucor nederlandicus, and Poitrasia circinans, were found in soil and freshwater samples. All species are described based on morphological and molecular evidence. Backusella terrestris is characterized by globose or subglobose sporangiospores, a variable (globose, subglobose, oval, or oblong) columellae, chlamydospore production, and a maximum growth temperature of 34 °C. The distinct characteristics of the new species and their closely related species are discussed. An identification key to the Backusella species of Korea is also presented.